On a source of outgoing electrons in a pulsed gas discharge; Journal of Experimental and Theoretical Physics Letters; Vol. 85, № 2 - Mesyats G. A. Gennady Andreyevich (2007, 2007)
В фонде НТБ ТПУ отсутствует